Ozone/graphene oxide catalytic oxidation: a novel method to degrade emerging organic contaminant N, N-diethyl-m-toluamide (DEET) - Liu, Jia-Nan (Sci Rep, 2016)
N, N-diethyl-m-toluamide (DEET) is one of the important emerging contaminants that are being increasingly detected in reclaimed water as well as in drinking water sources. However, DEET is refractory to conventional biological treatment and pure ozone which is absent of hydroxyl radical. Current researches on the efficient removal of DEET are still quite limited. This study utilizes a novel method, namely ozone/graphene oxide (O(3)/GO), to investigate the effects on DEET removal in aqueous systems, especially in reclaimed water. The results indicate that the DEET degradation rate was significantly accelerated through the combined effect of GO and ozonation which can yield abundant hydroxyl radical, compared to pure ozone condition. According to hydroxyl radical scavenging experiments, hydroxyl radical was found to play a dominant role in synergistic removal of DEET. These findings can offer sound suggestions for future research on the removal of emerging organic contaminants. The information could also be beneficial to reclaimed water safety and sustainable management.